Contextualizing Hadith within the Socio-Cultural Reality of Indonesia Based on the Concept of Maqāṣid al-Sharī‘ah - Refki Saputra; Iik Arifin Mansurnoor; Ryan Bianda (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2026)
This article explores the contextualization of hadith within Indonesian socio-cultural realities using a maqāṣid al-sharī‘ah-based framework. It seeks to demonstrate how hadith interpretation can uphold textual authority while responsibly addressing evolving social contexts. Employing qualitative library research, the study analyzes literature on hadith studies, uṣūl al-fiqh, maqāṣid al-sharī‘ah, and Indonesian Islamic thought. The analysis is structured around three methodological tools: al-ta‘līl al-maqāṣidī, al-tafsīr al-maṣlaḥī, and al-tamyīz bayn al-maqāṣid wa al-wasā’il. The findings reveal that maqāṣid-based contextualization should not serve as a shortcut to justify modern preferences. Instead, it must involve thorough textual analysis, engagement with classical scholarship, identification of ‘illah and maṣlaḥah, and assessment of social consequences. For example, the hadith concerning Quraysh leadership suggests that legitimate leadership can be understood in terms of public authority and social unity. The hadith on disciplining children to perform prayer highlights that religious education is the primary objective, with physical punishment being a conditional means. Additionally, the hadith addressing gold and silver ribā illustrates that the goal of preventing injustice in value exchange remains relevant to modern currencies. This article offers an operational model for maqāṣid-based hadith contextualization in the Indonesian context.